Civic-military schools: expression of state negligence and vector of privatization of public education (Revista Contexto & Educação, 2023)
This text aims to analyze the political strategy of the National Program of Civic-Military Schools – PECIM, one of the main policies of the Jair Bolsonaro government, which was extinguished in July 2023, at the initiative of the current government of President Lula da Silva. The defenders of this policy use arguments to create consensus in society about the supposed quality of teaching, based on the performance of large-scale standardized exams, and about probable positive consequences for students to conquer the discipline, in addition to trying to create an expectation of violence and crime will be tackled within schools and in the surrounding communities, due to the police presence. This attempt to create a consensus around this vision is riddled with the desire to hide structural problems in Brazilian education, whose militarization only contributes to worsening. Two, among many of these problems, will be the object of this article. The first refers to the historical negligence identified in the untying of resources for education and the second refers to the project of business reformers in education, which is the privatization of public schools. But, militarization gives new contours to this project of emptying the public school as it contemplates in politics the cultural war, of neo-fascist cleavages.